Within and between day repeatability of the incremental shuttle walking test in patients with thoracic cancer - Wilcock, Andrew; Koon, Sim; Manderson, Cathann; Taylor, Vicky; Maddocks, Matthew (Elsevier, 2018)
Background: Breathlessness is common in patients with thoracic cancer but difficult to manage. The Incremental Shuttle Walking Test (ISWT) can help assess new treatments, but its repeatability has not been described in this group.